2018
DOI: 10.1002/jcp.26541
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid ameliorates CCl4‐induced liver fibrosis through the NOXs/ROS pathway

Abstract: Liver fibrosis is a reversible wound‐healing response that occurs after liver injury. NADPH oxidases (NOXs) and reactive oxygen species (ROS) which are expressed in hepatocytes (HCs), hepatic stellate cells (HSCs), and Kupffer cells (KCs) play an important role in the development of hepatic fibrosis. In in vitro studies, we had shown that ursolic acid (UA) could reverse liver fibrosis by inhibiting the activation of NOX‐mediated fibrotic signaling networks in HSCs. In this study, we verified that UA could alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…These results were also confirmed with animal experiments. Injection of NOX4 bioinhibitors into CCl 4 -induced liver fibrosis in mice reversed the progression of liver fibrosis [ 40 ]. Here, we used NOX4 knockout mice to better understand the role of NOX4 in the development of liver fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also confirmed with animal experiments. Injection of NOX4 bioinhibitors into CCl 4 -induced liver fibrosis in mice reversed the progression of liver fibrosis [ 40 ]. Here, we used NOX4 knockout mice to better understand the role of NOX4 in the development of liver fibrosis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The outstanding findings in this paper are that the anti-liver-fibrosis Chinese medicine UA also has a certain improvement effect on the intestinal microbiota disorder during liver fibrosis. Our group has previously confirmed that UA can protect liver tissue and reverse liver fibrosis in an animal model of liver fibrosis induced by CCl 4 37 . In addition, our previous experiments also found that UA can reduce intestinal damage and protect intestinal integrity during liver fibrosis.…”
Section: Discussionmentioning
confidence: 65%
“…A derivative of oleanolic acid has shown antifibrotic effects in rat livers [52]. Ursolic acid has shown to exhibit anti-fibrotic effects in the liver of mice and rats [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%